Effectiveness of porcine dermal collagen in giant hernia closure in patients with deleterious fascia constitution after orthotopic liver transplantation. (7th November 2014) - Werkgartner, Georg; Cerwenka, Herwig; Rappl, Thomas; Kniepeiss, Daniela; Kornprat, Peter; Iberer, Florian; Bacher, Heinz; Wagner, Mathias; Mischinger, Hans J.; Wagner, Doris
Summary Incisional hernias (IHs) occur universally after orthotopic liver transplantation (OLT). This study aimed to investigate the effectiveness of porcine dermal collagen (PDC) as a closing aid in giant hernias after OLT in a prospective trial. If direct closure (DC) was not feasible due to the hernia size and abdominal wall constitution, a PDC mesh was implanted. All patients from the PDC and DC groups were followed prospectively for 24 months. IH recurrence rates served as the primary endpoint, and the development of infections and wound healing disorders served as the secondary endpoints. Recurrence rate was 21% (4/19) in DC patients and 12% (2/16) in PDC patients (P = 0.045). Implant site infections occurred in five of PDC and one of DC patients (P < 0.05). All of them were managed with antibiotics; two of the PDC patients required surgical drainage. Histological analysis of PDC mesh biopsies indicated good angiogenesis and integration of the PDC into the abdominal wall. PDC was effective in our study for incisional hernia repair, and our results compared favourably with those of patients in whom direct hernia closure was feasible.